Russian Chronicles on the Moscow-Kazan Relations: An Experience of the Hermeneutic Research - A.V. Aksanov (Золотоордынское обозрение)
Research objective: This paper analyzes the problem of interpretation of the chronicle reports about the Moscow-Kazan relations and identifies the semantics of these reports by using the hermeneutic analysis of texts. Research materials: The author cites the examples of the sources’ misunderstanding. Researchers treated literally reports about the Kazan khanate foundation, which in fact were based on the reminiscences from biblical books and needed an allegorical interpretation. Scholars made similar mistakes in their interpretation of some of the reports about the Kazan campaigns in 1467, 1487, 1506, and 1552. In turn, the use of hermeneutic methods allows us to significantly supplement and even revise the picture of the Moscow-Kazan relations presented in the historians’ works. This paper demonstrates some features of the evolution of Russian chronicle writing that affected the nature of the representation of interstate relations. Period of the last third of the 15th century is described both by official and independent (provincial) chronicle vaults. In this, these sources describe the events in different ways. Official chronicles represented the Moscow-Kazan war of 1467–1469 as a religious confrontation ended with Russian victory, while independent sources described this war without religious connotations and pointed to the defeat of Moscow forces. The author also revealed significant differences in the description of the events in 1478 and 1487. Research results and novelty: In such a way, independent sources refute a number of official reports about the Moscow-Kazan relations in the last third of the 15th century. In turn, period of the first half of the 16th century is well documented only in the official chronicles since independent chronicles fell into decline during the strengthening of the united Russian State. Thus, the picture of the Moscow-Kazan relations of this period is unilateral since it is based on information of official chronicles, which, in many cases, can not be verified by alternative sources.